2,3-Difunctionalization of quinones: a gold-catalyzed cascade approach for trifluoromethyl-amination or sulfoximination - Sharma, Alpa; Govande, Vijaya; Mahajan, Shivangani; Sawant, Sanghapal D. (Chemical Communications, 2024)
A one-pot domino protocol employing gold(i) catalysis has been developed for the cascade trifluoromethyl-amination/sulfoximination of quinones. Togni I serves as the trifluoromethyl installing precursor, while amine or sulfoximine serves as the aminating source. Preliminary investigations suggest a mutual activation of Togni I and the amine precursor, facilitating the facile difunctionalization of quinones with excellent regioselectivity. Extensive substrate scope exploration demonstrates moderate to good yields of difunctionalized products. Application to the natural product Juglone highlights its potential for late-stage modifications in medicinal chemistry and drug discovery. A one-pot domino protocol employing gold(i) catalysis has been developed for the cascade trifluoromethyl-amination/sulfoximination of quinones.

C-H functionalization of imidazo[1,5-a]pyridines: a metal-free approach for methylene insertion to access C(sp2)-C(sp3)-H-C(sp2) bond formation - Mahajan, Shivangani; Sawant, Sanghapal D. (ACS Omega, 2024)
Formaldehyde has been used as a solvent and a source of carbon to insert a methylene group for bridging two imidazo[1,5-a]pyridine molecules without using any metal catalysis. This strategy has been extended on other alkyl-, aryl-, and heteroaryl aldehydes as well. This C(sp2)-C(sp3)-H-C(sp2) bond forming reaction proceeds via C(sp2)H functionalization of imidazo[1,5-a]pyridine and was applied on a wide range of substrates offering moderate to good yields of methylene-bridged/inserted bis-imidazo[1,5-a]pyridines. Most importantly, as an application, the bis-heteroarene product has been demonstrated as a ligand. The ligand-like behavior of bis-imidazo[1,5-a]pyridines has been demonstrated as an extension of current methodology. This reaction works well at the gram scale level.

Diastereoselective synthesis of functionalized spiroindolines via intramolecular ipso-iodocyclization/nucleophile addition cascade reactions of indole-tethered ynones - Bag, Debojyoti; Sawant, Sanghapal D. (Organic and biomolecular chemistry, 2024)
Herein, we describe a highly diastereoselective approach for synthesizing polyfunctionalized spiroindolines from indolyl-ynones involving an ipso-iodocyclization/nucleophile addition cascade. The developed strategy allows the formation of a spirocyclic core and the installation of two functional groups in a single operation. Also this strategy is accompanied by the generation of two C-C and one C-I bonds and two contiguous stereocenters.

Divergent synthesis of unsymmetrical Bis-heteroaryl ketones via base-promoted cascade reactions of 1,2-alkynedione-derived N-propargylic β-enaminones - Bag, Debojyoti; Saini, Sheetal; Rathod, Mahesh S.; Sawant, Sanghapal D. (JOURNAL OF ORGANIC CHEMISTRY, 2024)
Keywords: ASYMMETRIC-SYNTHESIS; heterocycles; intramolecular cyclization; pyrroles

I2-catalyzed three-component synthesis of 3-selenylated pyrazolo[1,5-a]pyrimidines - Choudhuri, Tathagata; Paul, Suvam; Sikdar, Papiya; Das, Sourav; Sawant, Sanghapal D.; Bagdi, Avik Kumar (New Journal of Chemistry, 2024)
A straightforward protocol has been developed to access 3-selenylated pyrazolo[1,5-a]pyrimidines from readily available amino pyrazoles, chalcones, and diaryl/dialkyl diselenides. This I-2-catalyzed methodology is highly useful for synthesizing a wide range of functionalized 3-(aryl/alkylselanyl)pyrazolo[1,5-a]pyrimidine derivatives. Mechanistic investigation disclosed that iodine catalysis is very important in both the cyclization process as well as in the C-H selenylation step. Moreover, the developed reaction conditions are also applicable for the cyclization of amino pyrazole with enaminone followed by C-H selenylation in one pot. The use of simple reagents and catalyst, wide substrate scope, mild and metal-free reaction conditions, and practical applicability are the attractive facets of this approach.

Modular synthesis of unsymmetrical indolyl diketones from ynediones via sequential aza-Michael addition/C-H functionalization - Naveed, Abdul; Bag, Debojyoti; Sawant, Sanghapal D. (Organic & Biomolecular Chemistry, 2024)
Herein, we disclose an efficient approach for the synthesis of unsymmetrical indolyl diketones from easily accessible 1,2-alkynediones involving a sequential aza-Michael addition/C-H Functionalization process. The two-step, one-pot strategy involves the aza-Michael addition of an aniline generating the N-aryl enaminones followed by iodine-mediated C-H functionalization.

Discovery and biological evaluation of nitrofuranyl-pyrazolopyrimidine hybrid conjugates as potent antimicrobial agents targeting Staphylococcus aureus and methicillin-resistant S. aureus - Saini, Sapna; Reddy, G. Lakshma; Gangwar, Anjali; Kour, Harpreet; Nadre, Gajanan G.; Pandian, Ramajayan; Pal, Sunny; Nandi, Utpal; Sharma, Rashmi; Sawant, Sanghapal D. (RSC Medicinal Chemistry, 2025)
Nitrofuran and pyrazolopyrimidine-based compounds possess a broad antimicrobial spectrum including Gram-positive and Gram-negative bacteria. In the present work, a series of conjugates of these scaffolds was synthesized and evaluated for antimicrobial activity against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA). Many compounds showed MIC values of <= 2 mu g ml-1, with compound 35 demonstrating excellent activity (MICs: 0.7 and 0.15 mu g ml-1 against S. aureus and MRSA, respectively) and safety up to 50 mu g ml-1 in HepG2 cells. Compound 35 also exhibited no hemolytic activity, biofilm eradication, and effectiveness against efflux-pump-overexpressing strains (NorA, TetK, MsrA) without resistance development. It showed synergistic effects with vancomycin (S. aureus) and rifampicin (MRSA). Mechanistic studies revealed that compound 35 exhibits good membrane-targeting abilities, as evidenced by DAPI/PI staining and scanning electron microscopy (SEM). In an intracellular model, it reduced bacterial load efficiently in both S. aureus and MRSA strains. With a strong in vitro profile, compound 35 demonstrated favorable oral pharmacokinetics at 30 mg kg-1 and potent in vivo anti-MRSA activity, highlighting its potential against antibiotic-resistant infections.

Divergent synthesis of 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) using DMSO as a single carbon synthon - Sikdar, Papiya; Das, Sourav; Saini, Sheetal; Sawant, Sanghapal D.; Bagdi, Avik Kumar (Organic & Biomolecular Chemistry, 2025)
A divergent approach has been explored for synthesizing 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) using DMSO as a C1 synthon. A library of 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) has been synthesized using CuOAc and AcOH, respectively. The reaction progressed through a radical pathway. The usefulness of 3-formylpyrazolo[1,5-a]pyrimidines in synthesizing a zaleplon derivative has been demonstrated.

Interrupted borrowing hydrogen strategy enabled aminomethylation and direct cross-dehydrogenative coupling strategy enabled dicarbonylation reactions of imidazo[1,5-a]pyridines - Mahajan, Shivangani; Bag, Debojyoti; Kour, Harpreet; Sawant, Sanghapal D. (Chemical Communications, 2025)
Herein, we disclose the development of novel aminomethylation and dicarbonylation reactions of imidazo[1,5-a]pyridines. The developed aminomethylation strategy involves a Pd-catalyzed interrupted borrowing hydrogen strategy by utilizing MeOH as the methylene source. A wide variety of imidazo[1,5-a]pyridines and secondary amines were explored for the developed strategy. The established imidazo[1,5-a]pyridine dicarbonylation strategy involves a catalyst/additive-free direct cross-dehydrogenative coupling reaction between imidazo[1,5-a]pyridines and 2-oxoaldehydes.

Isobavachalcone ameliorates Alzheimer disease pathology by autophagy-mediated clearance of amyloid beta and inhibition of NLRP3 inflammasome in primary astrocytes and 5x-FAD mice - Kour, Dilpreet; Khajuria, Parul; Sharma, Kuhu; Sharma, Alpa; Sharma, Ankita; Ali, Syed Mudassir; Wazir, Priya; Ramajayan, P.; Sawant, Sanghapal D.; Nandi, Utpal; Ahmed, Zabeer; Kumar, Ajay (Frontiers in Pharmacology, 2025)
Background and Aim Alzheimer's disease (AD) progresses with A beta plaque deposition and neuroinflammation. Given the complexity of AD pathology, single-target therapies have frequently failed in clinical trials. We hypothesized that a multitarget approach could yield better therapeutic outcomes. To this end, we identified isobavachalcone (IBC), a natural compound with dual pharmacological activity in reducing A beta plaques and neuroinflammation.Experimental Procedure Primary astrocytes were isolated from 3 to 4 days old C57BL/6J mice pups for in-vitro assays, while in-vivo studies were conducted on 5x-FAD mice. Protein alterations were evaluated using ELISA, western blotting, immunocytochemistry, and immunohistochemistry. Behavioral analyses included the radial arm maze, open field, and rotarod tests. Data from all in vitro and in vivo experiments were analyzed by using one-way ANOVA and post-hoc Bonferroni tests.Results In-vitro analyses in astrocytes demonstrated that IBC at 5 and 10 mu M concentrations induce AMPK phosphorylation through CAMKK2, promoting autophagy and inhibiting the NLRP3 inflammasome in primary astrocytes. IBC-treated astrocytes exhibited significant clearance of extracellular amyloid beta. Mechanistic studies highlighted autophagy as a key factor in reducing both NLRP3 inflammasome activity and A beta levels. Two months of treatment of 5x-FAD mice with IBC at 25 and 50 mg/kg significantly improved cognitive functions, as evidenced by enhanced memory and motor performance in behavioral tests. Subsequent brain tissue analysis revealed that IBC upregulated autophagic proteins to reduce the brain's amyloid beta levels, resulting in decreased expression of neuroinflammation markers.Conclusion IBC effectively ameliorates AD pathology through autophagy-mediated clearance of A beta and suppressing neuroinflammation in 5x-FAD mice.
Keywords: Alzheimer disease; Amyloid beta; Autophagy; isobavachalcone; neuroinflammation; NLRP3 inflammasome

Novel pyrazole derivatives as inhibitors of Leishmania donovani: an integrated approach combining in vitro analysis and mechanistic insights - Kumari, Diksha; Kour, Jaspreet; Kumar, Anuj; Sangral, Monica; Singh, Shashank K.; Sawant, Sanghapal D.; Singh, Kuljit (Bioorganic Chemistry, 2025)
Leishmaniasis is a neglected tropical disease that continues to be a global public health problem, leading to a disastrous impact on poor rural people. The present therapeutic arsenal faces the limitations of drug resistance and toxicity concerns, raising a great need to identify novel chemical scaffolds that are potent, non-toxic, and cost-effective. Heterocycles comprise a distinctive class of molecules exhibiting a wide array of physical, chemical, and biological characteristics and occupy a prominent position in pharmaceutical applications. In the present study, we aimed to investigate three series of pyrazole derivatives synthesized previously by our group for their anti-leishmanial potential against Leishmania donovani parasites. Primarily, 29 compounds were evaluated using an Alamar blue dye-based assay for their inhibitory potency, out of which six molecules (4a, 4b, 4c, 4j, 7a, and 7d) were active with >50 % growth inhibition at a 50 mu M dose. Among them, three molecules (4b, 4j, and 7d) showed remarkable leishmanicidal potency with 50 % inhibitory concentration (IC50) in the range of 5 to 13 mu M. Toxicity analysis revealed that the potential hit (4j) represented a promising cytocompatibility profile along with noteworthy activity against L. donovani intracellular amastigotes. Furthermore, the in-depth mechanistic evaluation using scanning electron microscopy, reactive oxygen species (ROS) generation, mitochondrial membrane potential (Delta Psi m) determination, ATP quantification, cell cycle analysis, and lipid accumulation assay confirms the inhibitory potential of compound 4j. Thus, the present study represents pyrazole derivatives as a potential scaffold for the development of novel chemotherapeutics against leishmaniasis.
Keywords: Cell death; drug discovery; FACS analysis; leishmaniasis; Pyrazole derivatives; Reactive Oxygen Species (ROS); scanning electron microscopy

Synthesis of isatins via oxone® /TBAI-mediated on-water oxidation of indoles - Khajuria, Pratiksha; Bag, Debojyoti; Sawant, Sanghapal D. (Synthesis-Stuttgart, 2025)
Isatins and their derivatives are important scaffolds in a wide range of pharmaceuticals, bioactive compounds, and functional materials. Herein we describe a new strategy for the synthesis of isatins from indoles via Oxone (R)/TBAI-mediated oxidative dearomatization of indoles in water. The strategy works well with a variety of N-protected indoles and azaindoles.
Keywords: dearomatization; indoles; isatins; Oxidation; Water

Cu(ii)/I2 mediated synthesis of α-keto esters via C(sp2)-C(sp) bond cleavage of 1,2-alkynediones followed by C-O bond formation - Naveed, Abdul; Sawant, Sanghapal D. (New Journal of Chemistry, 2026)
Herein, we disclose an efficient method for the synthesis of alpha-keto esters through a copper(ii)/iodine-mediated reaction. The transformation involves the selective cleavage of the C(sp2)-C(sp) bond of 1,2-alkynediones, which is subsequently followed by C-O bond formation with alcohols. This protocol offers a broad substrate scope, accommodating a wide range of substrates to furnish the desired alpha-keto esters in good yields.

Elucidating the potential of novel class biphenyl-phenyl acetate, IDD-AN-A1, an inhibitor targeting Isocitrate Lyase in Mycobacterium tuberculosis: a target to lead approach - Negi, Anjali; Perveen, Summaya; Kour, Harpreet; Sawant, Sanghapal D.; Sharma, Rashmi (Bioorganic Chemistry, 2026)
Isocitrate lyase (ICL), a pivotal enzyme of the glyoxylate shunt pathway in Mycobacterium tuberculosis (Mtb), represents an attractive target for the development of new anti-tuberculosis (TB) therapeutics. In this study, we identified 2-methoxy-4-((nitrosooxy)methyl)phenyl 2-(2-fluoro-[1,1 `-biphenyl]-4-yl)propanoate (IDDAN-A1) as a potent inhibitor of Mtb ICL. The compound exhibited strong activity against Mtb, with a minimum inhibitory concentration of 6.25 mu g/mL, and demonstrated potent inhibition in enzyme-based assays targeting ICL. Molecular docking studies further supported Mtb ICL as the potential molecular target of this compound. Cytotoxicity and hemolytic assays revealed a favorable safety profile for the compound with selectivity index >10. In combination studies, it exhibited additive and synergistic activity with the frontline drug Rifampicin and Delamanid respectively. Additionally, ex vivo assays simulating the intracellular environment of the pathogen demonstrated strong inhibitory potency. In vitro inhibition studies further confirmed the bacteriostatic nature of the compound across different concentrations. Collectively, these findings demonstrate that this molecule possesses promising anti-tuberculosis activity by targeting the ICL enzyme in Mtb.
Keywords: Anti-tuberculosis activity; Ex vivo; Isocitrate lyase; tuberculosis